Socio-Psycho-Pedagogical Characteristics of Preschoolers - Садырова, М.С.; Сарыбаева, А.Б. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2019)
This article discusses the socio-psychological and pedagogical characteristics of preschool children. In each age period examples and systematic representations about features of development and abilities of perception of preschool children, and also features of formation of thinking and cognitive activity are affected. At the same time, it is noted that the leading activity is the game, considering the issue of socializa- tion of a child of preschool age. It promotes emotional, mental, volitional and personal development of the child. Playing a child, exploring the world, learns social roles and behaviors. Through the knowledge of the environment, the world the child demonstrates his mental actions. That is, through the game the child begins to realize his dream. Thanks to his imagination, he begins to achieve some success. All this begins with the fact that the child from an early age to learn about the world through the game. Depending on the growth of the child, the nature of the game changes (worsens). For example, a four-year-old child tolerates the behavior of adults and imitates them. During the game, he plays action scenes. The game will plot. By the age of six or seven, the child will have a predominant role-playing game . The essence of the game-the separation of roles. Children approaching the age of seven, enter into the game certain rules.